Updates in Liver Cancer 2017
DOI: 10.5772/66454
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells and Aldehyde Dehydrogenase 1 in Liver Cancers

Abstract: The cancer stem cell (CSC) theory posits that a small population of cells with stem celllike features is responsible for tumor growth, resistance, and recurrence in many malignancies. This theory could be a useful paradigm for designing innovative targeted drug therapies. Liver cancer is the ifth most common cancer worldwide, with hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) as the predominant forms. Hepatic stem/progenitor cells are believed to be the origin of HCCs and CCAs; however, this rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…For further confirmation of the correlation between perindopril and LCSCs, we investigated the expression of EpCAM (epithelial cell adhesion molecule) a marker of liver cancer stem cell ( Yamashita et al, 2009 ), and ALDH1, the enzyme that has been linked to stem cell and cancer stem cell population Tomita et al, 2017 . Our results revealed that ALDH1 expression was induced by perindopril or sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…For further confirmation of the correlation between perindopril and LCSCs, we investigated the expression of EpCAM (epithelial cell adhesion molecule) a marker of liver cancer stem cell ( Yamashita et al, 2009 ), and ALDH1, the enzyme that has been linked to stem cell and cancer stem cell population Tomita et al, 2017 . Our results revealed that ALDH1 expression was induced by perindopril or sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH is the main enzymatic system responsible for the clearance of acetaldehyde from the hepatocytes in the liver tissue. It is involved in retinoic acid signaling pathway known as differentiation of the hepatocytes (Tomita et al 2017). ALDH1-expressing cells may serve as a useful differentiation biological marker for hepatocellular carcinoma rather than as a CSC marker.…”
Section: A Functional Properties Of Lcscsmentioning
confidence: 99%